Pengembangan Pakan Plus Vitamin C dan Probiotik Untuk Ikan Lele Pada Kelompok Pembudidaya Ikan Tani Subur Desa Gunung Melati - Indira Fitriliyani; Siswanto Siswanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The target partners are the Tani Subur fish cultivator group that conducts catfish farming in tarpaulin ponds. In particular, the problem with rearing fish in tarpaulin ponds is the management of water quality which has an impact on taste and also low yields. The real effort that will be made to overcome these problems is to make efforts to manage water quality with a technological approach and the addition of vitamins in feed to improve fish health which has an impact on increasing crop yields. The activities carried out are 1) Application of feed technology in the management of catfish cultivation in tarpaulin ponds 2) Application of water quality management technology in the management of catfish cultivation in tarpaulin ponds and technical counseling, and 4) demonstration/practice activities and mentoring. Community partnership program service activities aim to transfer technology through technical training on albumin extract processing and utilization of by-products. The training method is counseling and demonstration which aims to provide knowledge and skills to the target audience. The follow-up plan of the training activity is the formation of creative businesses that increase the income of cultivator group members. This touch of technology is expected to increase the profit margins of pokdakan members which are expected to increase their confidence to develop this business in the future.